KETERAMPILAN KERJA ILMIAH MAHASISWA PENDIDIKAN KIMIA FKIP UNIVERSITAS TANJUNGPURA KALIMANTAN BARAT - Uray Rafika Siti Amalia; Husna Amalya Melati; Ira Lestari (Orbital: Jurnal Pendidikan Kimia, 2020)
Scientific work skills are one skill needed students as prospective educators to be able to face the demands of education 21st century. The purpose of this study to describe work skills Scientific students of Chemical Education FKIP Tanjungpura University on the material salt hydrolysis. The form of research used is descriptive research. Based on the method, this research uses descriptive analysis method. The subjects of this study were students of Chemical Education FKIP University Tanjungpura Class of 2018, amounting to 48 people. The instrument used namely a matter of scientific work skills and interview guidelines. Based on the category of skills obtained by the average KKI chemistry education students class of 2018 in the skilled category (62.5%). From the aspect of KKI, students chemical education formulates the problem in the skilled category (74.74%), formulate a hypothesis in the category of skilled enough (57.75%), analyze the data in the skilled category (64.65%), and formulating conclusions in the sufficient category skilled (45.05%). The implication of this research is that the research results can be used as input for lecturers to pay attention to appropriate learning models to improve students scientific work skills.